On Cinderella Men and Peaceful Warriors: “Sportainment” in American Mainstream Cinema - Radošinská, Jana (Communication Today, 2018)
Being one of the portmanteau words related to media entertainment, “sportainment” is a term that refers to the processes of merging sports and entertainment within the media sphere, predominantly for commercial purposes. Even though the concept is mostly discussed in terms of various forms of reality TV, live broadcasting of sports or globally successful spectacular sporting events such as the Olympic Games, there are many other forms of sportainment to consider. The author reflects on sportainment and its use in the present-day American mainstream film production. The aim of the article is to offer a set of theoretical outlines which are related to sport and its social, cultural and media frameworks, as well as knowledge on sports feature films produced in Hollywood and their thematic aspects. That is why the second part of the text addresses the ways various sports and athletes are portrayed in American mainstream films. The author works with the basic assumption that the current forms and variations of so-called sports dramas made in Hollywood apply multiple practices of genre hybridisation, and they thus tend to involve a wide variety of topics, ideas and heroes which may or may not be primarily focused on sport.